La tutela europea - Ángeles González-Fernández (Mélanges de la Casa de Velázquez, 2018)
From Montesquieu to Merkel an idea spanned Europe: the inability of Spaniards and Portuguese to be fully European and to participate in the rational and civilising order that governs the conduct of the Community. It was therefore thought best to subject the Iberian peoples to supervision so that, through a process of re-education, they could overcome this quasi-natural ineptitude. Assuming this perception of Iberia as a single, undifferentiated entity, the Community partners approached the integration of Spain and Portugal into the then European Communities as a unique process and part of this supervisory logic. The purpose of the article will be to analyse the persistence and mutation of these stereotypes in the negotiating process for accession to the European Communities.